Perempuan berswatantra menghadapi perubahan iklim dengan literasi ecopsychology feminism - Santoso, Indriyani; Kurniawan, Rizal; Asrila, Agitia Kurniati; Sari, Ayuthia Mayang (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2025)
Women are a group that is vulnerable to becoming victims of the impacts of climate change, the availability of air to meet sanitation needs, disasters that can occur at any time, and secondary impacts from economic problems that may arise. This research illustrates how literacy can strengthen women, open their minds, change paradigms about the environment, and even move women to try to be active and independent in responding to the impacts of climate change. Using qualitative methods, researchers carried out inductive coding on the results of interviews with five people with the highest New Ecological Paradigm Scale scores from sixty-six subjects selected using the criteria of women aged 18-40 years who liked to read literacy in the form of novels by female writers from Indonesia. Word Frequency analysis found that five words had context and formed the theme of this research, namely women, nature, mothers, characters, and the environment. This research reveals how feminist ecopsychological literacy can change views, determine attitudes, and mobilize Indonesian women to be pro-environmental and independent in responding to climate change, which causes changes in the natural environment.